Вовка - добрая душа: стихи / А. Л. Барто ; худ. : В. Чижиков - Барто Агния Львовна (Планета детства, 2005)
Экземпляры: 1, 10 ф. (12.11.08г.) / Инвентарный номер: 44741 / Цена: / Сис.шифр: Р 2 / Авт.знак: Б 26 / ББК: Р 2